Organ-preserving treatment of early rectal cancer - S. V. Chernyshov; O. A. Maynovskaya; Yu. A. Shelygin; Ye. G. Rybakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To generalize scientific data and to develop modern concept on the issue of diagnosis, staging and treatment of early rectal cancer. Summary. The world-wide issues of early rectal cancer are discussed in the review. Diagnostic methods and staging of the early cancer and premalignant states are discussed. Prospects of improvement of early rectal cancer treatment approach are outlined, advantages of the rectum-preserving techniques are justified. Conclusion. Early rectal cancer is rarely observed neoplasm that may be the main cause for diagnostic and staging difficulties. So far the choice of surgical method for early rectal cancer is a subject for discussion, at the same time the choice of method is determined not only by the tumor invasion depth, but also by the presence of risk factors for regional lymph node involvement.